2003
DOI: 10.1097/01.asn.0000077402.95720.b4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Galectin-3 in Diabetic Nephropathy

Abstract: Abstract. The advanced glycosylation end products (AGE) participate in the pathogenesis of nephropathy and other diabetic complications through several mechanisms, including their binding to cell surface receptors. The AGE receptors include RAGE, the macrophage scavenger receptors, OST-48 (AGE-R1), 80K-H (AGE-R2), and galectin-3 (AGE-R3). Galectin-3 interacts with the ␤-galactoside residues of cell surface and matrix glycoproteins via the carbohydrate recognition domain and with intracellular proteins via pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 43 publications
2
77
0
4
Order By: Relevance
“…27 GaL3 was shown to mediate the endocytotic uptake of modified lipoproteins 15 and to be a component of the AGE-receptor complex expressed in macrophages. 16 The functional interaction of GaL3 (AGE-R3) with AGE-R1 and AGE-R2 receptors 28 suggested the possible interaction with AGEbinding proteins. 29 Thus a putative sequence of events may start with the migration of monocytes into the artery wall, triggering GaL3 up-regulation in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…27 GaL3 was shown to mediate the endocytotic uptake of modified lipoproteins 15 and to be a component of the AGE-receptor complex expressed in macrophages. 16 The functional interaction of GaL3 (AGE-R3) with AGE-R1 and AGE-R2 receptors 28 suggested the possible interaction with AGEbinding proteins. 29 Thus a putative sequence of events may start with the migration of monocytes into the artery wall, triggering GaL3 up-regulation in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Maeda et al showed that galectin-3 induced hepatic stellate cells transdifferentiation into myofibroblasts via the mitogenactivated protein kinase/extracellular signal-regulated kinase (ERK)-ERK 1/2 signaling pathway and, at variance with galectin-1, in a protein kinase C-and A-dependent manner [53], whereas MacKinnon et al showed that galectin-3 ablation reduced alveolar epithelial cell EMT in response to TGF-β1 [50]. In addition, galectin-3 plays a complex role in the modulation of immune/inflammatory function, with distinct pro-inflammatory actions, but also with relevant anti-inflammatory effects which predominate under chronic conditions [7]. In acute settings, galectin-3 favors the inflammatory response against microbial infections.…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 99%
“…Extracellular galectin-3 interacts via the CRD [5] with the β-galactoside residues of several extracellular matrix (ECM) and cell surface glycoproteins [6]; this is the classical lectin-glycoconjugate interaction. Conversely, interactions of intracellular galectin-3 occur via peptide-peptide associations mediated by its N-terminus domain, though also the CRD may be involved at this level [7]. These structural properties enable galectin-3 to bind several proteins, thus exerting multiple functions which make it a broad-spectrum biological response modifier involved in several disease conditions [8] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated in two pre-clinical models of advanced DN that macrophages indeed had re-polarized locally in the tissue towards a phenotype more resembling a mixed M2 to M1/M2-like phenotype with significantly reduced CD11c in combination with enhanced galectin-3 expression [69]. Macrophage galectin-3 strengthen TGFβR signalling by retaining cell surface expression of TGF-β receptors and thus the newly polarized diabetic kidney macrophage might provide novel insight to understand the tissue remodelling processes occurring in DN [133,134]. …”
Section: Diabetic Complicationsmentioning
confidence: 99%